Local Heat Transfer Dynamics in the In-Line Tube Bundle under Asymmetrical Pulsating Flow - Aigul Haibullina; Aidar Khairullin; Denis Balzamov; Vladimir Ilyin; Veronika Bronskaya; Liliya Khairullina (Energies, 2022)
The pulsating flow is one of the techniques that can enhance heat transfer, therefore leading to energy saving in tubular heat exchangers. This paper investigated the heat transfer and flow characteristics in a two-dimensional in-line tube bundle with the pulsating flow by a numerical method using the Ansys Fluent. Numerical simulation was performed for the Reynolds number Re = 500 with different frequencies and amplitude of pulsation. Heat transfer enhancement was estimated from the central tube of the tube bundle. Pulsation velocity had an asymmetrical character with a reciprocating flow. The technique developed by the authors to obtain asymmetric pulsations was used. This technique allows simulating an asymmetric flow in heat exchangers equipped with a pulsation generation system. Increase in both the amplitude and the frequency of the pulsations had a significant effect on the heat transfer enhancement. Heat transfer enhancement is mainly observed in the front and back of the cylinder. At a steady flow in these areas, heat transfer is minimal due to the weak circulation of the flow. The increase in heat transfer in the front and back of the cylinder is associated with increased velocity and additional flow mixing in these areas. The maximum increase in the Nusselt number averaged over space and time in the entire studied range was 106%, at a pulsation frequency of 0.5 Hz and pulsation amplitude of 4.5. A minimum enhancement of 25% was observed at a frequency of 0.166 Hz and amplitude of 1.25.